Pengaruh Metode Demonstrasi Terhadap Peningkatan Hasil Belajar Peserta Didik Pada Materi Kalor dan Perpindahannya di Kelas XI SMA Negeri 8 Tikep - Abdul Rasid Sagemba; Marwiya Muksin (Peneliti.net, 2021)
This research is an experimental research. It was conducted at SMA Negeri 8 Tidore Islands in October 2021. The population in this study were students of class XI science at SMA Negeri 8 Tidore Islands which consisted of 20 students in the experimental class XI IPA 1 and 20 students in the control class XI IPA2. The experimental class is treated by using the demonstration learning method while the control class uses conventional learning. The design used in this research is the Pre-Test Post-Test Control Group Design. The research instrument was in the form of a learning outcome test. To test the hypothesis using the paired sample t-test. Data analysis was done descriptively. The results of this study indicate that: (1) In the experimental class the average value of the pretest is 35 while the average value of the posttest is 78, (2) In the control class the average value of the pretest is 35 while the posttest average value is 64. lower than the experimental class, (3) The average posttest value of the experimental class > control class is 78 > 64 which means that the experimental class learning outcomes are higher than the control class, in the paired t-test, the results obtained are sig. 2 tailed of 0.002 < 0.05 the use of the demonstration method on the concept of heat and its transfer is more effective